Infection associated with CDK4/6 inhibitors: a pharmacovigilance analysis of the FDA adverse event reporting system database - Chen, Jinhua; Tang, Linlin; Song, Wenping; Sun, Cuicui; Zhang, Wenzhou (Frontiers in Pharmacology, 2024)
Introduction Cyclin-dependent kinase 4 and 6 (CDK4/6) inhibitors are first-line treatments for hormone receptor-positive/human epidermal growth factor receptor 2-negative breast cancer. With their increasing clinical use, infection-related adverse events (AEs) associated with CDK4/6 inhibitors have been widely reported in recent years. This study aimed to analyze the occurrence of infections associated with the CDK4/6 inhibitors (palbociclib, ribociclib and abemaciclib) based on the real-world data from the US Food and Drug Administration Adverse Event Reporting System (FAERS) database. Methods Data were extracted from the FAERS database between 2015Q1 and 2022Q3. The clinical characteristics of patients with primary suspected infection-related AEs were analyzed. A disproportionality analysis was performed to investigate the potential association between AEs and CDK4/6 inhibitors. The influencing factors were evaluated using Pearson’s chi-square test. Results Reports of infection-related AEs associated with ribociclib accounted for 8.58% of the total reports of AEs associated with ribociclib, followed by palbociclib (2.72%) and abemaciclib (1.24%). Ribociclib (67.65%) was associated with more serious outcome events than palbociclib (30%) or abemaciclib (48.08%). The sex and age were not associated with outcome severity. Disproportionality analysis showed that fourteen, sixteen and two infection-related preferred terms were detected for palbociclib, ribociclib and abemaciclib, respectively. Conclusion Infection-related AEs were highly associated with three CDK4/6 inhibitors, especially palbociclib and ribociclib, based on the real-world data from the FAERS database. However, further causality assessment is required.